Evaluation of stress cracking on geomembranes after accelerated tests - Lavoie, Fernando Luiz; Bueno, Benedito de Souza; Lodi, Paulo César [UNESP] (Universidad Nacional de Colombia, 2014)
This paper presents results of stress cracking tests performed in high density polyethylene (HDPE) geomembranes (GM). Stress cracking tests were performed in accordance to ASTM D5397: Notched Constant Tensile Load Test (NCTL) and Single Point-Notched Constant Tensile Load Test (SP-NCTL). Tests were conducted to the fresh sample at 50ºC (standard test) and at 70ºC (accelerated condition) in order to compare the SC values. Results from accelerated tests (NCTL) showed, for instance, a total economy of 390 hours (comparing load stages of 25% yield stress) to perform the tests.

Este trabajo presenta resultados de fisuración bajo tensión realizados con geomembranas (GM) de polietileno de alta densidad (HDPE). Las pruebas de tensión fueron realizados de acuerdo a la norma ASTM D5397: Notched Constant Tensile Load Test (NCTL) and Single Point-Notched Constant Tensile Load Test (SP-NCTL). Estos ensayos fueron realizados en muestras de control a 50 º C (ensayo padrón) y a 70 º C (condición acelerada) para comparar valores de fisuración bajo tensión. Los resultados de estos ensayos acelerados (NCTL) mostraron una economía total de 390 h (comparando etapas de carga de 25% de la tensión de ruptura) para los ensayos realizados.

Dyna, year 81, Nro. 183, pp. 223-228. Medellin, February, 2014. ISSN 0012-7353
Evaluación de fisuración bajo tensión de geomembranas pos ensayos acelerados
Keywords: HDPE geomembranes; Stress cracking; Accelerated tests; Geomembranas de polietileno de alta densidad; Fisuración bajo tensión; Pruebas aceleradas